Design and Research of the Three-posture Adjustable Multi-functional Integrated Wheelchair Bed - Li Yanan; Zhou Xiaochen; Zhang Baoxu; Xu Guoxin; Tan Cao; Zhao Yanjun (Jixie chuandong)
To change the physical harm caused by the constant posture of disabled people for a long time, a three-posture adjustable multi-functional integrated wheelchair bed was proposed, which realized the timely transformation of sitting, standing and lying. The device includes a bed chair conversion mechanism, an auxiliary standing mechanism and a bed body lifting mechanism. The kinematic mathematical model of each mechanism was established, and the kinematic simulation was carried out based on the Matlab software. The virtual prototype model of the wheelchair bed was constructed, and the Admas simulation was carried out. The physical prototype of the multi-functional wheelchair bed was built, and its motion stability was verified experimentally. The rationality of the prototype was verified by comparing the test curve with the simulation curve, providing a basis for further research on the wheelchair bed.